PHYTOCHEMICAL COMPOSITION AND USE OF ACHILLEA MILLEFOLIUM IN TRADITIONAL MEDICINE (Scientific journal of the Fergana State University, 2025)
This review article focuses on the phytochemical composition and traditional medicinal uses of Achillea millefolium. The chemical composition of the plant has been found to contain biologically active compounds such as flavonoids, alkaloids, essential oils, tannins, coumarins, and sesquiterpenes. These compounds make A. millefolium a valuable medicinal plant with anti-inflammatory, analgesic, antibacterial, antifungal, and antioxidant properties. The article provides detailed information on its use in traditional medicine, including stopping bleeding, addressing gastrointestinal issues, alleviating nervous system disorders, and treating respiratory diseases. The data highlight the medicinal importance of A. millefolium and emphasize the need for further research and clinical trials to develop new therapeutic strategies.